Respuesta :

Step-by-step explanation:

The general formula of a quadratic equation is

[tex]a {x}^{2} + bx + c[/tex]

while the general formula for finding the vertex is

[tex]a({x - h})^{2} + k[/tex]

first of all, you have to set the value of

[tex]x = \frac{ - b}{2a} [/tex]

From the given equation, a = 2; b = -12 and c = 13. therefore, x = -(-12)/2(2) = 12/4 = 3

The 3 gotten is the answer for the value of h. To get k, substitute the value of h into the quadratic equation.

k = 2(3)^2 - 12(3) + 13 = -5

Therefore, the Vertex is V(h,k) = V(3,-5)